Alat Ukur Temperatur 5 Kanal Menggunakan Mikrokontroler 8031 - Tenggara, Herlianto; Kurniawan Susanto, Bayu; Thiang, Thiang (Institute of Research and Community Outreach, 2001)
This paper describes the designing of five channels instrument for temperature measurement. This instrument also has differential mode facility so the temperature difference between two points can be determined. This instrument was designed by using 8031 microcontroller for the temperature measurement processes. Generally%2C this instrument consists of two main parts. The first part is 8031microcontroller minimum system and the second one is sensor and transmitter circuit. This instrument uses LM35 temperature sensor and transmitter circuit is used to transmit the signal so the remote temperature measurement can be achieved. Experiment was done and the measurement data was recorded. The maximum error of temperature measurement that can be achieved is 1%B0C. The experiment was also done by using 30 meters transmitter cable and it show good result too. Abstract in Bahasa Indonesia : Pada makalah ini dijelaskan tentang perencanaan dan pembuatan alat ukur temperatur dengan fasilitas lima kanal. Alat ukur ini juga dilengkapi dengan fasilitas diferensial mode sehingga dapat mengetahui perbedaan suhu di dua tempat. Mikrokontroler 8031 digunakan sebagai alat bantu yang mengatur semua proses pengukuran temperatur. Secara umum%2C sistem ini terdiri atas dua bagian utama yaitu minimum sistem 8031 itu sendiri dan rangkaian sensor beserta rangkaian transmiternya. Sensor temperatur yang digunakan adalah LM35. Pada sistem ini dilengkapi rangkaian transmiter agar dapa digunakan untuk pengukuran temperatur jarak jauh. Pengujian sistem telah dilakukan dengan melakukan perekaman data pengukuran. Hasil pengujian menunjukkan bahwa kesalahan pengukuran temperatur yang paling besar adalah 1%B0C. Selain itu pengujian juga dilakukan dengan menggunakan kabel transmitter yang panjangnya 30 meter dan menghasilkan pengukuran yang sama.%0D%0A%0D%0A Temperature+Sensor%2C+Transmitter%2C+8031+Microcontroller